MORFO-ANATOMI Commelina erecta L. (COMMELINACEAE) DARI TAMAN WISATA ALAM SURANADI LOMBOK BARAT. - Mulyaningsih, Tri; Sholehah, Nayla Qoni’Atun; Karima, Maulida; Izzati, Inayatul; Putri, Windi Septiya; Salsabila, Puspa Dwi; Setyaningrum, Tri Wahyu; Muspiah, Aida (Samota Journal of Biological Sciences, 2025)
Commelina erecta, a herbaceous plant of the Commelinaceae family, is found in humid tropical habitats and is known for its adaptability. This study aims to analyze morpho-anatomical characters C. erecta, from Suranadi Nature Tourism Park, West Lombok. The method used was macro and microscopy technique, slides made with hand free cross section of fresh preparations, and used single staining Toluidine Blue O (TBO) 0.025%. Microscopic characterization of root, stem, sheath, petiole, leaf margin. The analysis showed that roots have radial vascular bundles, composed of poliarch. The anatomical structure of the stem of C. erecta is a transitional form from dicotyledon to monocotyledon, characterized by the presence of a clear separation of the cortex and stele tissues which are separated by a layer of continuous natural sclerenchymatous tissue.